2005
DOI: 10.1111/j.1463-5224.2005.04061.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of bacterial microorganisms in the conjunctival sac of clinically normal dogs and dogs with ulcerative keratitis in Fortaleza, Ceará, Brazil

Abstract: The results of our study are directly applicable to initiate rational, preventive and therapeutic measures with greater accuracy in dogs with corneal ulcer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
102
5
16

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(144 citation statements)
references
References 13 publications
13
102
5
16
Order By: Relevance
“…The grampositive bacteria displayed a predominance of 86.6% among the strains isolated, in accordance with findings for a series of domestic and wild animals (PRADO et al, 2005;SANTOS et al, 2009;SPINELLI et al, 2010;BONELLI et al, 2014;ORIÁ et al, 2014).…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…The grampositive bacteria displayed a predominance of 86.6% among the strains isolated, in accordance with findings for a series of domestic and wild animals (PRADO et al, 2005;SANTOS et al, 2009;SPINELLI et al, 2010;BONELLI et al, 2014;ORIÁ et al, 2014).…”
Section: Resultssupporting
confidence: 68%
“…In the present study, Corynebacterium sp. was the fourth most common microorganism isolated, which has also been demonstrated in eyes of dogs (PRADO et al, 2005) and sheep (BONELLI et al, 2014) without eye problems, but at a lower prevalence as that observed in our animals.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations